Preparation method of high-enthalpy reticulated cross-linked solid-solid phase change energy storage material

CN122878735APending Publication Date: 2026-10-09FUJIAN TECHWORK TEXTILE CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611234248.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]因此,针对上述的问题,本发明提供一种高热焓网状交联型固-固相变储能材料的制备方法,解决现有纺织用相变调温材料因相变温度偏高、焓值不足、耐水洗性差及手感僵硬,难以满足贴身织物低温舒适调温需求的问题

Benefits of technology

1、在步骤S1和S2两段预聚中均采用PEG与聚己内酯三元醇(PCL Triol)的复合软段体系,并利用PCL三元醇的三官能度羟基作为内嵌交联点。一方面,PCL链段扰乱PEG规整结晶,有效抑制球晶生长,将熔融温度由纯PEG3000/2000的48℃-60℃降低至30℃-33℃,完全适配纺织服装的贴身使用场景;另一方面,PEG与PCL的双重结晶贡献使材料在低温区间内仍保持≥90J/g的高熔融焓,解决了传统交联型聚氨酯相变材料“降温度必降焓值”的技术矛盾。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878735A_ABST
    Figure CN122878735A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of material preparation methods, and provides a preparation method of a high-enthalpy reticular crosslinking solid-solid phase change energy storage material, which solves the problems that the existing phase change temperature adjusting materials for textiles are difficult to meet the low-temperature comfortable temperature adjusting demand of close-fitting fabrics due to the high phase change temperature, insufficient enthalpy, poor washing resistance and stiff hand feeling; the method comprises the following steps: S1, a mixture of PEG 3000 and polycaprolactone triol is used as a composite soft segment, pre-polymerization is carried out through dicyclohexyl methane diisocyanate, glycol, trihydroxymethyl propane and ethyl acetate are added to carry out chain extension reaction, and a solid-solid phase change polyurethane-based material is obtained; S2, a mixture of PEG 2000 and polycaprolactone triol is used as a soft segment, pre-polymerization is carried out, glycerol, a sulfonate type hydrophilic chain extender and ethyl acetate are added to carry out chain extension reaction, and a high-flexibility water-based polyurethane is obtained; and S3, the two are mixed according to a mass ratio to obtain the high-enthalpy reticular crosslinking solid-solid phase change energy storage material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material preparation methods, and in particular to a method for preparing a high-enthalpy network cross-linked solid-solid phase change energy storage material. Background Technology

[0002] Against the backdrop of rapidly increasing demand for energy-saving temperature control materials across various industries, phase change energy storage materials (PCS) have become a core functional material for realizing the spatiotemporal transfer of heat energy and reducing system temperature control energy consumption. In recent years, they have been widely used in fields such as industrial waste heat recovery, building temperature control, electronic heat dissipation, and special protection. Among them, solid-solid PCS, with its unique advantages of not generating a liquid phase during phase change, no leakage risk, small volume change, and long cycle life, significantly reduces the sealing requirements of packaging containers compared to traditional solid-liquid PCS. It can be directly processed through blending, spinning, molding, and other processes, making it a research hotspot in the field of energy storage materials.

[0003] In the textile industry, the phase change temperature requirements for temperature-regulating fibers are concentrated in the comfortable temperature range of 20℃-40℃. Traditional solid-solid phase change materials, due to their excessively high phase change temperatures, cannot complete effective heat absorption / release cycles within the temperature range of daily human activities, thus hindering their long-term application in the textile and apparel industry. Previously, the industry mostly used microencapsulation of solid-liquid phase change materials to prepare temperature-regulating textile materials, but this approach has significant drawbacks: microcapsules are prone to rupture at high temperatures or under external force, leading to core material leakage, which greatly limits their application in the textile and apparel industry. Furthermore, microcapsule materials have poor affinity with textiles, requiring the addition of adhesives for bonding, which significantly affects the feel and breathability of the textiles.

[0004] Addressing the long-standing technical challenges in this industry, the development of a novel solid-solid phase change energy storage material that combines high enthalpy, suitable room temperature phase change range, and direct applicability to the textile and apparel industry has become a core technical problem that the functional textile materials industry urgently needs to solve. This is also the core research and development background of this invention patent.

[0005] Chinese Patent Publication No. CN112225858B discloses a hyperbranched waterborne polyurethane solid-solid phase change material and its preparation method. The following raw materials are weighed according to mass percentage: polyethylene glycol, polyisocyanate, hydrophilic chain extender, triol, neutralizing agent, and water. The weighed polyisocyanate is added to polyethylene glycol, and after stirring, a -NCO-terminated prepolymer is obtained. The weighed hydrophilic chain extender is added to the -NCO-terminated prepolymer, and after stirring, a hydrophilic chain-extended mixture is obtained. The weighed triol is added to the hydrophilic chain-extended mixture, and after stirring, a hyperbranched mixture is obtained. The weighed neutralizing agent is added to the hyperbranched mixture, and after stirring, a neutralized hyperbranched mixture is obtained. The weighed water is added to the neutralized hyperbranched mixture, and after stirring evenly, the hyperbranched waterborne polyurethane solid-solid phase change material is obtained. This preparation method can obtain hyperbranched waterborne polyurethane solid-solid phase change materials with good temperature regulation performance, but the soft segment only uses PEG with a single molecular weight, and the phase change temperature is too high, making it difficult to meet the comfort temperature regulation requirements of close-fitting textiles; at the same time, while the single hyperbranched cross-linked network structure improves the shape stability of the material, it often leads to a stiff feel and insufficient softness after the material is formed. Summary of the Invention

[0006] Therefore, in view of the above problems, the present invention provides a method for preparing a high enthalpy network cross-linked solid-solid phase change energy storage material, which solves the problem that existing textile phase change temperature regulating materials have high phase change temperature, insufficient enthalpy, poor water resistance and stiff hand feel, making it difficult to meet the low-temperature comfort temperature regulation requirements of close-fitting fabrics.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a high-enthalpy, cross-linked solid-solid phase change energy storage material includes the following steps: S1. The first polyether polyol is dehydrated under vacuum at 110℃-120℃ for 2 hours; then cooled to 60℃-70℃, dicyclohexylmethane diisocyanate is added and reacted for 1-2 hours, and then heated to 70-75℃ and reacted for 2-3 hours to form the first polyurethane prepolymer; then ethylene glycol, trimethylolpropane and ethyl acetate are added, and chain extension reaction is carried out at 70℃-90℃ for 2-3 hours, and ethyl acetate is removed by vacuum evaporation to obtain solid-solid phase change polyurethane-based material; S2. The second polyether polyol is dehydrated under vacuum at 110℃-120℃ for 2 hours; then cooled to 60℃-70℃, dicyclohexylmethane diisocyanate is added and reacted for 1-2 hours, and then heated to 70-75℃ and reacted for 2-3 hours to form the second polyurethane prepolymer; then glycerol, sulfonate-type hydrophilic chain extender and ethyl acetate are added, and the chain extension reaction is carried out at 70℃-90℃ for 2-3 hours. After cooling to 40℃, a neutralizing agent is added for neutralization, and then deionized water is added for emulsification. Ethyl acetate is removed under reduced pressure to obtain a highly flexible waterborne polyurethane material. S3. The solid-solid phase change polyurethane-based material prepared in step S1 and the highly flexible waterborne polyurethane material prepared in step S2 are mixed in a mass ratio of (1-2):(0.5-1) and stirred evenly to obtain a high enthalpy network cross-linked solid-solid phase change energy storage material with a solid content of 20%-30%. The high enthalpy network cross-linked solid-solid phase change energy storage material has a melting temperature of 30℃-33℃ and a melting enthalpy ≥90J / g; The first polyether polyol is a mixture of PEG 3000 and polycaprolactone triol, wherein the mass ratio of PEG 3000 to polycaprolactone triol is 3-8:1; The second polyether polyol is a mixture of PEG 2000 and polycaprolactone triol, wherein the mass ratio of PEG 2000 to polycaprolactone triol is 3-8:1.

[0008] Furthermore, the molecular weight of the polycaprolactone triol is 1000-3000.

[0009] Furthermore, in step S1, the molar ratio of the first polyether polyol to dicyclohexylmethane diisocyanate, ethylene glycol, and trimethylolpropane is 1:(1.5-2):(0.8-1):0.1.

[0010] Furthermore, in step S2, the molar ratio of the second polyether polyol to dicyclohexylmethane diisocyanate, glycerol, and sulfonate-type hydrophilic chain extender is 1:(1.2-1.6):(0.05-0.2):(0.15-0.35).

[0011] Furthermore, in step S2, the sulfonate-type hydrophilic chain extender is sodium 1,4-butanediol-2-sulfonate or sodium 1,2-dihydroxy-3-propanesulfonate.

[0012] Furthermore, in step S2, the neutralizing agent is triethylamine, ammonia, or N-methylpyrrolidone.

[0013] Furthermore, the high enthalpy network cross-linked solid-solid phase change energy storage material is used for padding or coating finishing of temperature-regulating textiles.

[0014] By adopting the aforementioned technical solution, the beneficial effects of the present invention are as follows: 1. In both S1 and S2 prepolymerization stages, a composite soft segment system of PEG and polycaprolactone triol (PCL Triol) is used, with the trifunctional hydroxyl groups of PCL Triol serving as intercalation crosslinking points. On one hand, the PCL segments disrupt the regular crystallization of PEG, effectively inhibiting spherulite growth and reducing the melting temperature from 48℃-60℃ for pure PEG3000 / 2000 to 30℃-33℃, perfectly suited for the close-fitting application scenarios of textiles and apparel. On the other hand, the dual crystallization contribution of PEG and PCL allows the material to maintain a high melting enthalpy of ≥90J / g in the low-temperature range, resolving the technical contradiction of traditional crosslinked polyurethane phase change materials where "lowering the temperature inevitably leads to a decrease in enthalpy."

[0015] 2. A combination of ethylene glycol and trimethylolpropane forms a moderately dense network crosslink, ensuring the material maintains shape stability at high temperatures and preventing PEG leakage. A combination of glycerol and a sulfonate-type hydrophilic chain extender provides the necessary cohesive strength while retaining excellent chain flexibility and film-forming properties. This design gives the final blended material both the structural stability of a solid-solid phase change and the processing adaptability and soft feel of waterborne polyurethane.

[0016] 3. Using sulfonate-type hydrophilic chain extenders, the sulfonic acid groups have a higher degree of ionization, which can achieve excellent self-emulsification effect at a lower dosage. The resulting emulsion has a narrower particle size distribution and better storage stability. At the same time, sulfonates have better heat resistance than carboxylates, which is beneficial for the high-temperature baking process in subsequent textile finishing.

[0017] 4. The process route of stepwise prepolymerization of solid-solid phase change substrate and highly flexible waterborne polyurethane material followed by mixing is adopted. Compared with the traditional one-step copolymerization, this method can independently control the crystallization behavior, crosslinking density and hydrophilicity of the two polymers, and flexibly adjust the phase change enthalpy, flexibility and solid content of the final material by adjusting the mixing ratio of the two. Attached Figure Description

[0018] Figure 1 This is the DSC diagram of the high enthalpy network cross-linked solid-solid phase change energy storage material in this embodiment of the invention. Detailed Implementation Example 1

[0019] refer to Figure 1 A method for preparing a high-enthalpy network cross-linked solid-solid phase change energy storage material includes the following steps: S1. The first polyether polyol was dehydrated under vacuum at 120°C for 2 hours; then cooled to 60°C, and dicyclohexylmethane diisocyanate was added and reacted at this temperature for 1 hour. The temperature was then raised to 70°C and reacted at this temperature for 3 hours to form the first polyurethane prepolymer. Subsequently, ethylene glycol, trimethylolpropane, and ethyl acetate were added, and the chain extension reaction was carried out at 70°C for 2 hours. The ethyl acetate was removed by vacuum evaporation to obtain the solid-solid phase change polyurethane-based material. S2. The second polyether polyol was dehydrated under vacuum at 120°C for 2 hours; then cooled to 60°C, and dicyclohexylmethane diisocyanate was added and reacted at this temperature for 1 hour. The temperature was then raised to 70°C and reacted at this temperature for 3 hours to form the second polyurethane prepolymer. Subsequently, glycerol, sulfonate-type hydrophilic chain extender and ethyl acetate were added, and the chain extension reaction was carried out at 70°C for 2 hours. After cooling to 40°C, a neutralizing agent was added for neutralization. Then, deionized water was added for emulsification, and ethyl acetate was removed under reduced pressure to obtain a highly flexible waterborne polyurethane material. S3. The solid-solid phase change polyurethane-based material prepared in step S1 and the highly flexible waterborne polyurethane material prepared in step S2 are mixed in a mass ratio of 2:1 and stirred evenly to obtain a high enthalpy network cross-linked solid-solid phase change energy storage material with a solid content of 30%. The high enthalpy network cross-linked solid-solid phase change energy storage material has a melting temperature of 31.2℃ and a melting enthalpy of 95.6 J / g. The first polyether polyol is a mixture of PEG 3000 and polycaprolactone triol, wherein the molecular weight of the polycaprolactone triol is 2000; and the mass ratio of the PEG 3000 to the polycaprolactone triol is 5:1. The second polyether polyol is a mixture of PEG 2000 and polycaprolactone triol, wherein the molecular weight of the polycaprolactone triol is 2000; and the mass ratio of PEG 2000 to polycaprolactone triol is 5:1.

[0020] In step S1, the molar ratio of the first polyether polyol to dicyclohexylmethane diisocyanate, ethylene glycol, and trimethylolpropane is 1:2:0.9:0.1.

[0021] In step S2, the molar ratio of the second polyether polyol to dicyclohexylmethane diisocyanate, glycerol, and sulfonate-type hydrophilic chain extender is 1:1.4:0.1:0.25.

[0022] In step S2, the sulfonate-type hydrophilic chain extender is sodium 1,4-butanediol-2-sulfonate.

[0023] In step S2, the neutralizing agent is triethylamine.

[0024] The high-enthalpy network cross-linked solid-solid phase change energy storage material is used for padding and finishing of temperature-regulating textiles.

[0025] Depend on Figure 1 It can be seen that the high enthalpy network cross-linked solid-solid phase change energy storage material prepared in Example 1 has a melting phase change temperature of 31.2℃ and a melting enthalpy as high as 95.6J / g, which can be well applied to the temperature regulation needs in the textile and apparel field. Example 2

[0026] The difference from Example 1 is as follows: In step S3, the solid-solid phase change polyurethane-based material prepared in step S1 is mixed with the highly flexible waterborne polyurethane material prepared in step S2 at a mass ratio of 1.5:1.

[0027] Other technical solutions are the same as in Example 1.

[0028] The high enthalpy network cross-linked solid-solid phase change energy storage material prepared in Example 2 has a melting phase change temperature of 30.5℃ and a melting enthalpy as high as 92.3J / g. Example 3

[0029] The difference from Example 1 is as follows: In step S1, the molar ratio of the first polyether polyol to dicyclohexylmethane diisocyanate, ethylene glycol, and trimethylolpropane is 1:1.5:1:0.1. In step S2, the sulfonate-type hydrophilic chain extender is sodium 1,2-dihydroxy-3-propanesulfonate; the neutralizing agent is ammonia. In step S3, the solid-solid phase change polyurethane-based material prepared in step S1 is mixed with the highly flexible waterborne polyurethane material prepared in step S2 at a mass ratio of 1.2:1.

[0030] The high enthalpy network cross-linked solid-solid phase change energy storage material prepared in Example 3 has a melting phase change temperature of 31.8℃ and a melting enthalpy as high as 91.5J / g.

[0031] Although the invention has been specifically shown and described in conjunction with preferred embodiments, those skilled in the art should understand that various changes in form and detail may be made to the invention without departing from the spirit and scope of the invention as defined in the appended claims, all of which shall be within the scope of protection of the invention.

Claims

1. A method for preparing a high-enthalpy network cross-linked solid-solid phase change energy storage material, characterized in that, Includes the following steps: S1. The first polyether polyol is dehydrated under vacuum at 110℃-120℃ for 2 hours; then cooled to 60℃-70℃, dicyclohexylmethane diisocyanate is added and reacted for 1-2 hours, and then heated to 70-75℃ and reacted for 2-3 hours to form the first polyurethane prepolymer; then ethylene glycol, trimethylolpropane and ethyl acetate are added, and chain extension reaction is carried out at 70℃-90℃ for 2-3 hours, and ethyl acetate is removed by vacuum evaporation to obtain solid-solid phase change polyurethane-based material; S2. The second polyether polyol is dehydrated under vacuum at 110℃-120℃ for 2 hours; then cooled to 60℃-70℃, dicyclohexylmethane diisocyanate is added and reacted for 1-2 hours, and then heated to 70-75℃ and reacted for 2-3 hours to form the second polyurethane prepolymer; then glycerol, sulfonate-type hydrophilic chain extender and ethyl acetate are added, and the chain extension reaction is carried out at 70℃-90℃ for 2-3 hours. After cooling to 40℃, a neutralizing agent is added for neutralization, and then deionized water is added for emulsification. Ethyl acetate is removed under reduced pressure to obtain a highly flexible waterborne polyurethane material. S3. The solid-solid phase change polyurethane-based material prepared in step S1 and the highly flexible waterborne polyurethane material prepared in step S2 are mixed in a mass ratio of (1-2):(0.5-1) and stirred evenly to obtain a high enthalpy network cross-linked solid-solid phase change energy storage material with a solid content of 20%-30%. The high enthalpy network cross-linked solid-solid phase change energy storage material has a melting temperature of 30℃-33℃ and a melting enthalpy ≥90J / g; The first polyether polyol is a mixture of PEG 3000 and polycaprolactone triol, wherein the mass ratio of PEG 3000 to polycaprolactone triol is 3-8:1; The second polyether polyol is a mixture of PEG 2000 and polycaprolactone triol, wherein the mass ratio of PEG 2000 to polycaprolactone triol is 3-8:

1.

2. The preparation method of a high enthalpy network cross-linked solid-solid phase change energy storage material according to claim 1, characterized in that, The molecular weight of the polycaprolactone triol is 1000-3000.

3. The preparation method of a high-enthalpy network cross-linked solid-solid phase change energy storage material according to claim 1, characterized in that, In step S1, the molar ratio of the first polyether polyol to dicyclohexylmethane diisocyanate, ethylene glycol, and trimethylolpropane is 1:(1.5-2):(0.8-1):0.

1.

4. The preparation method of a high enthalpy network cross-linked solid-solid phase change energy storage material according to claim 1, characterized in that, In step S2, the molar ratio of the second polyether polyol to dicyclohexylmethane diisocyanate, glycerol, and sulfonate-type hydrophilic chain extender is 1:(1.2-1.6):(0.05-0.2):(0.15-0.35).

5. The preparation method of a high enthalpy network cross-linked solid-solid phase change energy storage material according to claim 1, characterized in that, In step S2, the sulfonate-type hydrophilic chain extender is sodium 1,4-butanediol-2-sulfonate or sodium 1,2-dihydroxy-3-propanesulfonate.

6. The preparation method of a high enthalpy network cross-linked solid-solid phase change energy storage material according to claim 1, characterized in that, In step S2, the neutralizing agent is triethylamine, ammonia, or N-methylpyrrolidone.

7. The preparation method of a high enthalpy network cross-linked solid-solid phase change energy storage material according to claim 1, characterized in that, The high-enthalpy network cross-linked solid-solid phase change energy storage material is used for padding or coating finishing of temperature-regulating textiles.

Citation Information

Patent Citations

  • A hyperbranched waterborne polyurethane solid-solid phase change material and its preparation method

    CN112225858B